Iona Iverson's rules for commuting - Pooley, Clare (Pamela Dorman Books/Viking, 2022)
"Nobody ever talks to strangers on the train. It's a rule. But what would happen if they did? From the New York Times bestselling author of The Authenticity Project, a heartwarming novel about unexpected friendships and the joy of connecting. Every day Iona, a larger-than-life magazine advice columnist, travels the ten stops from Hampton Court to Waterloo Station by train, accompanied by her dog, Lulu. Every day she sees the same people, whom she knows only by nickname: Impossibly-Pretty-Bookworm and Terribly-Lonely-Teenager. Of course, they never speak. Seasoned commuters never do. Then one morning, the man she calls Smart-But-Sexist-Manspreader chokes on a grape right in front of her. He'd have died were it not for the timely intervention of Sanjay, a nurse, who gives him the Heimlich maneuver. This single event starts a chain reaction, and an eclectic group of people with almost nothing in common except their commute discover that a chance encounter can blossom into much more. It turns out that talking to strangers can teach you about the world around you--and even more about yourself"--